Gold-catalyzed bidirectional access to planar heptacyclic benzobispyrido(1,2-α)indoles and benzobispyrrolo(1,2-α)quinolines for materials science - Heckershoff, Robin; Eberle, Lukas; May, Garrett; Krämer, Petra; Rominger, Frank; Rudolph, Matthias; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2022)
Our recently developed gold-catalyzed synthesis of indolo[1,2-a]quinolines was successfully expanded towards bidirectional approaches, enabling access to two heptacyclic structural motifs. In the case of benzobispyrido[1,2-a]indoles, previously inaccessible modifications of the only known representative were made possible. In addition, the synthesis of a new class of nitrogen-containing heptacycles - namely benzobispyrrolo[1,2-a]quinolines - was achieved by applying alkynylated benzodipyrrole derivatives as starting materials. All new compounds alongside with their corresponding precursors were fully characterized and their properties were investigated by X-ray crystallography, photophysical measurements and computational methods. The study revealed important structure-effect relationships between the solid-state structures and the observed photophysical properties, e. g. aggregation-induced emission and solid-state fluorescence.
First published: 06 September 2022
Gesehen am 20.12.2022